IMPLEMENTASI LATIHAN RESISTANCE BAND TERHADAP KEMAMPUAN SMASH BOLA VOLI SISWA EKSTRAKURIKULER SMA N 8 PADANG - Pisha Orlanda; Yogi Arnaldo Putra; Yogi Setiawan; Vega Soniawan (Fakultas Ilmu Keolahragaan Unimed, 2026)
This study aims to determine the effect of resistance band training on the volleyball smash ability of extracurricular students at SMA Negeri 8 Padang. The smash is the main attacking technique in volleyball, which requires strength, accuracy, and good movement coordination. The research method used was a quasi-experiment with a one-group pre-test and post-test design. The research sample consisted of 8 students selected using purposive sampling. The research instrument used a volleyball smash ability test. The treatment consisted of resistance band training given during 16 meetings. The data were analyzed using the Liliefors normality test and the t-test at a significance level of α = 0.05. The results showed that the average smash ability score on the initial test (pre-test) was 7 and increased to 15 on the final test (post-test). The t-test results showed that the t-count value of 14.737 was greater than the t-table value of 1.895, so it can be concluded that there was a significant effect of resistance band training on the volleyball smash ability of students in the extracurricular program at SMA Negeri 8 Padang. Thus, resistance band training can be used as an effective training alternative to improve smash ability in volleyball.